STRUKTUR KOMUNITAS SERANGGA PADA TANAMAN KOPI (Coffea robusta L) DI DESA BELIMBING KECAMATAN MUARA PINANG SUMATERA SELATAN - Apriani Sari, Rini (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2014)
Research ofÂ  insect of community structure on coffe Â (Coffea robusta L.) in Belimbing Village Muara Pinang Â SubdistrictÂ  Â Sumatera Selatan Province, conductedÂ  September tillÂ  October Â 2013, to saw insect species of coffe plant, density, ferquency, importan value index and Â diversity index. The research used direct survey method, and data sampling with purpossive in Â transect.Â  Â The result showed gated 15 species Â Â insects are Valanga nigricornis, Anax sp, Neoconocephalus sp, Oecopylla smaragdina, Gryllus miratus, Hydrophilus sp, Â Photuris sp, Zizinia sp, Mantis sp, Phyllophaga sp,Â  Hypothenemus hampei, Â Bactrocera conformis, Â Sexava sp, Tipula sp and Polistes sp. Oecopylla smaragdina Â was dominant species, with importan value index Â 34,94%Diversity index was medium categhory with Â Hâ value Â 2,22.Â Key words :Â Â  diversity, insect, Â Vigna sinensis